DESKRIPSI MOTIVASI BELAJAR SISWA KELAS XI SMA NEGERI 06PONTIANAK - Sulastri Sulastri; Abas Yusuf; Purwanti Purwanti (Universitas Tanjungpura, 2019)
AbstractThe background of this research is the problem of achievement motivation which is a problem that deserves attention, because the lack of achievement motivation is not just an indication of a decline in enthusiasm and enthusiasm for learning but can affect the achievement of learning goals. Based on a survey conducted at SMA Negeri 6 Pontianak, there were many students who did not yet have achievement motivation, for example lack of confidence, lack of creativity in actualizing themselves.